Biochemical and Microstructural Properties of Lizardfish (Saurida tumbil) Scale Collagen Extracted with Various Organic Acids - Abdul Aziz Jaziri; Rossita Shapawi; Ruzaidi Azli Mohd Mokhtar; Wan Norhana Md. Noordin; Nurul Huda (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The purpose of this research was to extract collagen from the scales of lizardfish (Sauridatumbil) using various acids. Acetic acid-extracted collagen (AScC) produced a higher yield (1.8 mg/g)than lactic acid-extracted collagen (LScC) and citric acid-extracted collagen (CScC) although not significantly different (p> 0.05). All extracted collagens were categorized as type I collagens with the presence of alpha chains (α1 and α2) based on the SDS-PAGE profiles. The triple-helical structure of the collagen was maintained in the AScC, LScC, and CScC as confirmed by the FTIR spectra. The UV-vis and X-ray diffraction spectra observed in all collagens were in agreement with previous work on fish scale and calfskin (commercial) collagens. The thermal stability of AScC (Tmax= 31.61◦C) was greater than LScC (Tmax= 30.86◦C) and CScC (Tmax= 30.88◦C). The microstructure of acid-extracted collagens was characterized as complex, fibrous, and multilayered, with irregular sheet-like structures.All samples were highly soluble in acidic pH (1.0–4.0) and in low concentrations of NaCl (0–20 g/L).In conclusion, the lizardfish scale collagen, particularly AScC, may be used as an alternative to terrestrial animal collagen.